Effect of a brief, group and virtual treatment based on Acceptance and Commitment Therapy for the anger regulation and the psychological inflexibility reduction in Colombian young adults - Gallego Villa, Óscar Mauricio (2023)
Background: At present, interventions for the management of problematic anger regulation and psychological inflexibility in affected young adults are scarce. Objetive: to evaluate the efficacy of a brief intervention, in a group and virtual format, for anger regulation and psychological inflexibility reduction. Method: A group of 40 Colombian young adults (40% male; 60% female; M= 25.3 years; SD= 3.35) were randomly assigned to one of two conditions: Acceptance and Commitment Therapy-based intervention for anger regulation and psychological inflexibility reduction and waiting list. Experiential avoidance, cognitive fusion, connection to the present moment, values, and perception of negative effects of problematic anger expression were assessed. Results: Significant differences with large effect sizes were found in the experiential avoidance, cognitive defusion, contact with the present moment, and obstruction in values variables. The variables of progress in values and perception of the effects of anger presented changes in the experimental group, but not in their comparison with the control group. Conclusions: the results provided evidence on the efficacy of this intervention, although more studies are required to confirm this.